IMF Staff papers : Volume 36 No. 3. (IMF Staff Papers; IMF Staff Papers ;, 1989)
Although accommodative policies and widespread indexation may account for the persistence of high inflation, they cannot explain changes in the inflation rate. The causes of such changes for the high-inflation episodes immediately preceding the recent 'heterodox' attempts at stabilization in Argentina, Brazil, and Israel are examined by computing historical decompositions of these episodes based on vector autoregressions, distinguishing between the 'fiscal' and 'balance of payments' views of their causes. In all three cases, nominal exchange rate shocks played the dominant role in triggering an acceleration of inflation. [JEL 134].